Utilization of Sugarcane Bagasse as a Substrate for Plankton Productivity - E. Sugumaran, M.V. Radhakrishnan (Recent Research in Science and Technology, 2010)
The present investigation has been conducted to evaluate the effect of sugarcane bagasse as an artificial substrate for plankton productivity. Sugarcane bagasse bundles (Length 50 cm; diameter 4cm) of 5 kg were hung in a large cement tank (5x5x1 cm) with 15 cm soil base with well water. Water quality parameters (Temperature, pH, dissolved Oxygen, Alkalinity and dissolved carbondioxide) and plankton biomass were monitored for 15, 20, 40 and 60 days respectively. Bagasse substrate did not adversely affect water quality but variations in plankton density were noted. The result demonstrate that sugarcane bagasse can effectively use as a substrate for plankton productivity.